T Follicular Helper Cells Promote a Beneficial Gut Ecosystem for Host Metabolic Homeostasis by Sensing Microbiota-Derived Extracellular ATP - Perruzza, L.; Gargari, G.; Proietti, M.; Fosso, B.; D'Erchia, A.; Faliti, C.; Rezzonico-Jost, T.; Scribano, D.; Mauri, L.; Colombo, D.; Pellegrini, G.; Moregola, A.; et al. (2017)
© 2017 The Authors The ATP-gated ionotropic P2X7 receptor regulates T follicular helper (Tfh) cell abundance in the Peyer's patches (PPs) of the small intestine; deletion of P2rx7, encoding for P2X7, in Tfh cells results in enhanced IgA secretion and binding to commensal bacteria. Here, we show that Tfh cell activity is important for generating a diverse bacterial community in the gut and that sensing of microbiota-derived extracellular ATP via P2X7 promotes the generation of a proficient gut ecosystem for metabolic homeostasis. The results of this study indicate that Tfh cells play a role in host-microbiota mutualism beyond protecting the intestinal mucosa by induction of affinity-matured IgA and suggest that extracellular ATP constitutes an inter-kingdom signaling molecule important for selecting a beneficial microbial community for the host via P2X7-mediated regulation of B cell help.